2006
DOI: 10.1562/2005-09-01-ra-669
|View full text |Cite
|
Sign up to set email alerts
|

On the Correlation Between Hydrophobicity, Liposome Binding and Cellular Uptake of Porphyrin Sensitizers

Abstract: A crucial factor in choosing a porphyrin or analogous photosensitizer for photodynamic therapy (PDT) is its ability to incorporate into the cells. For hydrophobic compounds that partition passively into the cytoplasmic membrane, a partition coefficient between an organic solvent and water, P, is one factor that could be used to predict the molecule's ability to diffuse into biomembranes. We synthesized several porphyrins, modified with two, three or four meso-substituents and studied their spectroscopic and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 40 publications
4
58
0
Order By: Relevance
“…Several studies have shown that the cell membrane is one of the targets of ROS generated during the photodynamic process [41,[48][49][50][51]. PI is widely used to evaluate the membrane integrity [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the cell membrane is one of the targets of ROS generated during the photodynamic process [41,[48][49][50][51]. PI is widely used to evaluate the membrane integrity [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, only limited studies on the preparation of unsymmetrical systems thereof or porphyrin arrays amenable to further 3 functionalization have been published. In the context of our interest in the preparation of near-IR absorbers for applications in photodynamic therapy (PDT) [10] we have begun to explore the chemistry of these compounds with the goal in mind to make unsymmetrical and amphiphilic systems for use in preclinical studies [11][12][13].…”
mentioning
confidence: 99%
“…This allowed the synthesis of an extensive glycoporphyrin library which has been biologically evaluated and used to identify the intracellular localization of glycoporphyrins depending on the carbohydrate unit present [33] . For example, these preliminary results in biological testing showed that triglycosubstituted porphyrins lack the ability to be taken up by esophageal cancer cells possibly due to their high water solubility and reinforced that amphiphilicity of such systems is key to their ability to cross the lipid membrane [34][35][36][37][38][39][40][41][42] .…”
Section: Carbohydratesmentioning
confidence: 99%